Cytotoxic potential of vasoconstrictor experimental gingival retraction agents: in vitro study on primary human gingival fibroblasts - Nowakowska, D; Saczko, J; Kulbacka, J; Choromanska, A; Raszewski, Z (Folia biologica, 2012)
The aim of this in vitro study was to evaluate the cytotoxic effects of the vasoconstrictor experimental gingival retraction agents (VEGRAs) in a dynamic setting. The strong cytotoxic effects of the astringent-based conventional gingival retraction agents (ACGRAs) on human gingival fibroblasts (HGFs) in vitro was our motivation to evaluate the biocompatibility of the vasoconstrictor-based experimental gingival retraction agents (VEGRAs) for the selected minimally invasive chemical agent. These agents were used to create three self-made retraction gels. Human gingival fibroblasts (HGFs) were treated with two groups of retraction agents: 1) three α- and β-adrenergic agents (VEGRA-αβ-s) based on 0.1%, 0.01% and 0.05% HCl-epinephrine, and 2) seven α-adrenergic agents (VEGRA-α-s), including two commercially available 0.05% HCl-tetrahydrozoline solutions, one 0.05% HCl-oxymetazoline solution, 10% HCl-phenylephrine solution, and three new self-made experimental 0.05% HCl-tetrahydro zoline-based gels. The methyl thiazolyl tetrazolium (MTT) colorimetric assay was performed to determine the oxidoreductive mitochondrial function after 3, 5, 10 min and 24 h of incubation. The cytotoxic effect, measured by cell viability lower than the 50% threshold, was not observed at any time period, even 24 h after application of 0.05% HCl-tetrahydrozolinebased self-manufactured retraction gels. High cell viability values of human gingival fibroblasts after the treatment with the three self-made 0.05% HCl-tetrahydrozoline- based gels may serve as a basis for further studies aimed at selecting the best retraction agents biocompatible with gingival margin tissues.
Keywords: Cell Survival; adstringencia; Humans; Epinephrine; buněčná smrt; Gingiva; lidé; Cells, Cultured; Vasoconstrictor Agents; gingiva; Astringents; Gingival Retraction Techniques; adrenalin; kultivované buňky; vazokonstriktory; fibroblasty; techniky odtažení gingivy; Cell Death; viabilita buněk; Fibroblasts